Circulating MicroRNA-21 Correlates With Left Atrial Low-Voltage Areas and Is Associated With Procedure Outcome in Patients Undergoing Atrial Fibrillation Ablation. (June 2018) - Zhou, Qifeng; Maleck, Carole; von Ungern-Sternberg, Saskia N.I.; Neupane, Balram; Heinzmann, David; Marquardt, Jonathan; Duckheim, Martin; Scheckenbach, Christian; Stimpfle, Fabian; Gawaz, Meinrad; Schreieck, Jürgen; Seizer, Peter; et al.
Abstract : Background: Atrial fibrosis is a hallmark of arrhythmogenic structural remodeling in patients with persistent atrial fibrillation (AF) and is negatively correlated with procedure outcome in patients undergoing ablation. However, noninvasive methods to determine the extent of atrial fibrosis are limited. Here, we used microRNA (miRNA) expression analysis to detect markers of left atrial low-voltage areas (LVAs) in patients with persistent AF undergoing catheter ablation. Methods: We performed 3-dimensional voltage mapping in 102 patients (average age 62.1±13.1 years, CHA2 DS2 -VASc score of 2.3±1.6, LA size 41.5±5.7 mm) undergoing ablation for persistent AF and determined the extent of left atrial low-voltage. LVAs were defined if bipolar electrogram amplitudes were <0.5 mV during sinus rhythm. Before ablation, we obtained a blood sample, isolated miRNAs, and profiled them on a miRCURY LNA Universal RT microRNA PCR Human panel. Results: Sixty-nine miRNAs were identified in all samples, with an average of 123 miRNAs detectable per sample. We found that the serum concentration of miR-21, a miRNA that has been previously linked to cardiac fibrosis development, was strongly associated with the extent of LVAs determined by voltage mapping. We could confirm that LVAs were negatively correlated with ablation success in a 1-year follow-up. In addition, miR-21 serum levels were associated with AF-free survival after catheter ablation. Conclusions: Circulating miR-21 correlates with left atrial LVAs and is associated with procedure outcome in patients with persistent AF undergoing ablation.